An Empirical Study on the Influence of Employment Policies on Gender Inclusion in Indian Military - Munshi, Anupama (Prabandhan: Indian Journal of Management, 2018)
Inclusion is to value every individual, provide similar access and opportunities to all, eliminate discrimination and other obstacles in involvement. Pearpoint and Forest (n.d.) described inclusion as an inevitable change. With this underlying idea, the present paper sought to understand the impact of employment policies on gender inclusion in the Indian military and derive meaningful insights for the policy makers in this area. The paper analyzed the influence of employment policies on gender inclusion on the basis of data collected from the survey of officers belonging to the different Corps of the Indian Army by using factor analysis and one way MANOVA. Factor analysis gave a three factor solution comprising of Job Content, Inclusive Climate, and Equal Treatment. The findings indicated that the employment policies do have an influence on the inclusion of women in military. This study seems to be the first in analyzing the effect of employment policies of the military with respect to gender inclusion in the Indian context.